2019
DOI: 10.1158/0008-5472.can-18-2049
|View full text |Cite
|
Sign up to set email alerts
|

Loss of FOXP3 and TSC1 Accelerates Prostate Cancer Progression through Synergistic Transcriptional and Posttranslational Regulation of c-MYC

Abstract: Although c-MYC and mTOR are frequently activated proteins in prostate cancer, any interaction between the two is largely untested. Here, we characterize the functional cross-talk between FOXP3-c-MYC and TSC1-mTOR signaling during tumor progression. Deletion of Tsc1 in mouse embryonic fibroblasts (MEF) decreased phosphorylation of c-MYC at threonine 58 (pT58) and increased phosphorylation at serine 62 (pS62), an observation validated in prostate cancer cells. Conversely, inhibition of mTOR increased pT58 but de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 51 publications
(106 reference statements)
1
26
0
1
Order By: Relevance
“…Additionally, TSC1 was validated to be downregulated in MM samples, and abolished miR-19b-induced MM development [31]. The tumor suppressor role of TSC1 was also corroborated in prostate cancer and highgrade serous ovarian carcinoma [32,33]. Consistently, we found that TSC1 enrichment was apparently declined in MM as well.…”
Section: Discussionsupporting
confidence: 79%
“…Additionally, TSC1 was validated to be downregulated in MM samples, and abolished miR-19b-induced MM development [31]. The tumor suppressor role of TSC1 was also corroborated in prostate cancer and highgrade serous ovarian carcinoma [32,33]. Consistently, we found that TSC1 enrichment was apparently declined in MM as well.…”
Section: Discussionsupporting
confidence: 79%
“…Chen et al found that the high levels of NPRL2 gene expression in prostate cancer cells promote resistance to EVS (an inhibitor of the mTOR) by enhancing autophagy [25]. In addition, TSC1 was significantly associated with DFS in PCa, which is an essential component of the PI3K/ AKT/mTOR signaling pathway [26]. Among the 22 DFS-related ARGs, except for those mentioned above, other ARGs are either poorly investigated or have not been reported, which means our findings suggested further research for them is imperative.…”
Section: Discussionmentioning
confidence: 99%
“…24 HIF-1α, TWIST-1, ITGB-1, and Ki-67 expression levels were scored by two independent clinical doctors who had no prior knowledge of the prognosis or other clinicopathological variables, using a weighted Histoscore method, also known as the H-score. 25 Briefly, the percentage of positive cells per slide (0% to 100%), as the average of ten random fields (400x, diameter: 0.55mm) screened, and the dominant intensity pattern of staining (0, absent; 1, weak; 2, moderate; 3, intense) were measured for each tumor section. H-scores for each sample were determined by multiplying the staining intensity by the percentage of positive cells (range, 0 to 300).…”
Section: Immunohistochemical Evaluationmentioning
confidence: 99%